Pengaruh Terapi Dzikir dan Relaksasi Nafas dalam untuk Mengurangi Nyeri pada Pasien Fraktur Pasca Operasi - Dila Gustiana Handayani; Wulan Noviani; Hanif P. Naviasari (Sci-tech Journal, 2025)
Introduction: A fracture or break in a bone is usually produced by trauma, which can happen directly or indirectly. Typically, surgery is performed on fractured patients, which might cause discomfort. Deep breathing techniques with a mixture of Dhikr recitation, which is beneficial for rest and relaxes muscles, can be used to alleviate pain and enhance comfort in post-op fracture patients. This case study examined the use of a combination of dhikr treatment and deep breathing relaxation for post-operative fracture patients experiencing pain. Method: This study employed an evaluative design, namely a case study of post-op fracture patients experiencing discomfort. The intervention was implemented non-pharmacologically using deep breathing relaxation techniques and a mixture of Dhikr recitations, which can dramatically reduce pain in post-operative patients in 5-15 minutes. Results: After observing the administration using a combination of dhikr therapy and deep breathing exercise three times per day or when pain emerges, there were changes in pain as seen by blood pressure, pulse, and the pain scale, which can reduce. Conclusion: Dhikr therapy combined with deep breathing exercises helps alleviate pain in post-operative fracture patients.